Overview of Corporate Governance Research in India: A Bibliometric Analysis - Abhilash Abhilash; Sandeep S Shenoy; Dasharathraj K Shetty (Cogent Business & Management, 2023)
Though the Corporate Governance concept has gained paramount interest due to the spate of corporate scandals, there is a void in the literature in terms of a summary overview of corporate governance in the Indian context. The present study aims to provide a state-of-the-art summary of corporate governance in India. To do so, the study employs a bibliometric analysis with a systematic literature review approach with extensive use of Bibliometric R Packages and VOSViewer software. To this end, the study reviews a total of 344 articles published in the Scopus database between 2004 and 2022. Akin to this, the review performs performance analysis, science mapping, and network analysis. The findings show an increasing trend in publications since 2004 till date with an annual growth rate of 23.99%. The network analysis results delineate earnings management, gender diversity, ownership structure, board structure, board size, corporate governance, ownership, and firm performance as major research themes in this field. This study is the primary attempt to show the growth and evolution of CG research in India. Thus, the review contributes to the existing literature on CG at the country level and provides scope for further research. Also, the study findings help policymakers, academicians, and regulators to strengthen corporate governance practices in the country.
Keywords: 650; bibliometric analysis; Corporate governance; India; R package; systematic literature review